Optimization procedure for intelligent Internet of Things applications - Ahmed, Zeinab E.; Hasan, Mohammad Kamrul; Hassan Abdalla Hashim, Aisha; Saeed, Rashid A.; Mokhtar, Rania A.; Singh, Simar P.; Ghazal, Taher M. (IEEE, 2022)
Internet of Things (IoT) is basically the concept and terminology of vehicular communications for Vehicles are becoming increasingly available in the literature. Applications for these are efficient traffic management, driving safety, and information services, which offer new service functionalities to extend efficiency for the network. In IoV, the vehicles carry advanced components such as actuators, sensors, and controllers to provide vehicle control functions and intelligent decision-making. The connectivity among vehicles is through intercommunication between devices, intelligent systems in the environment, and sensors [3]. There are three elements for a network model of IoV: client, connection, and cloud. The optimization technique finds the optimal result for sophisticated challenges by diminishing or exploiting objective functions that stand on one or more decision parameters that achieve the objective function value. This paper proposes a GA-based energy optimization procedure and assesses the performance over existing optimization techniques for intelligent IoT applications.